On Domatic Energy of a Graph - K. B. Murthy; B. V. Dhananjayamurthy (International Journal of Mathematics And its Applications, 2017)
In this paper, Motivated by the partition energy and the minimum covering energy of a graph, we introduce domatic energy $E_d\left(G\right)$, of a graph $G$.